ChemInform Abstract: Iridium‐Catalyzed Hydrogenation of Carboxylic Acid Esters. Issue 13 (March 2015) - Junge, Kathrin; Wendt, Bianca; Jiao, Haijun; Beller, Matthias
Abstract A variety of esters is reduced for the first time selectively using an iridium pincer‐type complex as catalyst.